Optimization of a Portable Ligand-Free Optical Spectroscopy Method For SARS-Cov-2 Protein Detection - Fatin Hamimi Mustafa; Nik Yusnoraini Yusof; Mawaddah Mohd Azlan; Fariza Hanim Suhailin; Chan Yean Yean; Nik Mohd Noor Nik Zuraina; Mohd Zulkifli Salleh; Hironaga Uchida; Irneza Ismail; Rosline Hassan; Raja Kamarulzaman Raja Ibrahim; Mohd Adzir Mahdi (Elsevier BV, 2026)
Tier 2- Indexed by SCOPUS